Ultrasonography Is An Important Tool For The Diagnosis Of Acute Abdominal Disease In Children: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Acute abdominal pain in children presents a significant diagnostic challenge requiring rapid and accurate assessment to prevent morbidity. Ultrasonography (US) is increasingly used as the first-line imaging modality due to its safety, accessibility, and diagnostic precision.Objective: This systematic review aimed to evaluate the diagnostic accuracy, clinical effectiveness, and comparative performance of ultrasound in detecting acute abdominal conditions in children, including appendicitis, intussusception, and other surgical emergencies.Methods: Following PRISMA 2020 guidelines, a comprehensive search of PubMed, Scopus, Embase, Web of Science, and Google Scholar was conducted from inception to December 2025. Ten peer-reviewed studies meeting predefined inclusion criteria were analyzed. Diagnostic parameters (sensitivity, specificity, PPV, NPV, and accuracy) and clinical outcomes were synthesized narratively.Results: Across the ten studies, ultrasound demonstrated a sensitivity range of 58–99.6% and specificity range of 68–100%, with an overall diagnostic accuracy of 90–96%. Studies such as Roberts et al. (2024) and Hajalioghli et al. (2020) reported near-perfect diagnostic accuracy for appendicitis, while Bergmann et al. (2021) confirmed non-inferiority of point-of-care ultrasound (POCUS) compared to radiology-performed US.Ultrasound also enabled alternative diagnoses in up to 100% of negative cases (Lim et al., 2015).Conclusion: Evidence supports ultrasonography as a highly accurate, non-invasive, and indispensable diagnostic tool for pediatric acute abdominal disease, reducing unnecessary surgery and radiation exposure while improving clinical efficiency.